CHARACTERISTICS OF BO VA GOLD-SULPHIDE ORES, NORTHEAST VIETNAM - Anh, Tran Tuan (Vietnam Journal of Earth Sciences, 2014)
Characteristics of Bo Va gold-sulphide ores, Northeast Vietnam Research ore characteristics and chemical composition of the three ore zones in the Bo Va region imply that mineralization in the area belong toe gold-sulfide (Au-As) type, characterizing by strong positive correlation between arsenic and gold. Native gold in different types of ore deposits in Bo Va usually present as independent inclusions in ore minerals or fill in the spaces between the main ore mineral, mostly of small very small size, closely associated with arsenopyrites. Two types of native gold have been identified: the first type is characterized by Ag = 18.5 to 15 wt.%; the second type: content is about 10 wt.% Ag in composition. The presence of fine-grained gold not only in quartz sulfide but also the distribution of large quantities waste arsenopyrite-bearing shales have important implications for the navigating appropriate exploitation and extracting solutions. References Nguyễn Thế Cương (chủ biên), 1996: Đo vẽ bản đồ địa chất và tìm kiếm khoáng sản nhóm tờ Cao Bằng - Đông Khê tỷ lệ 1:50.000. Liên đoàn Địa chất Đông Bắc. Nguyễn Văn Quý, 2011: Gold. In Geology and Earth Resources of Việt Nam (Trần Văn Trị and Vũ Khúc - Editors), p.542-544; Publ. House for Science and Technology, 645pp. Petrov V.G và nnk, 1996: Đặc điểm cấu trúc trường quặng, các kiểu cấu trúc, hình thái của các mạch thạch anh chứa vàng mỏ Bó Va (Cao Bằng). Địa chất - Tài nguyên , công trình kỷ niệm 20 năm thành lập Viện Địa chất, 1: 361-367 Viện Địa chất - Hà Nội. Petrov V.G và nnk, 1996: Đặc điểm thành phần khoáng vật và giai đoạn tạo quặng ở mỏ Bó Va Cao Bằng. Địa chất - Tài nguyên, công trình kỷ niệm 20 năm thành lập Viện Địa chất, 1: 367-374 Viện Địa chất - Hà Nội. Phạm Đình Long (chủ biên), 1974: Bản đồ địa chất khoáng sản tờ Chinh Si - Long Tân tỷ lệ 1:200.000. Trần Trọng Hoà et al., 1997: Bo Va quartz-veins gold deposit in North Vietnam. Extended Abstract from Seminar on Geol. and Metallic Minerals. Hanoi. Trần Trọng Hòa, Borisenko A.S. (đồng chủ biên), 2006: Nghiên cứu phát hiện các kiểu quặng hóa vàng mới (Au-Sb-Hg) trên lãnh thổ MBVN. Báo cáo tổng kết đề tài HTQT do Viện KHCNVN hỗ trợ. Lưu trữ Viện Địa chất. Trần Trọng Hòa và nnk, 2013: Các tụ khoáng vàng - sulfide trong các thành tạo lục nguyên và lục nguyên carbonat rift Sông Hiến, Đông Bắc Việt Nam. Tuyển tập báo cáo Hội thảo KC.08/11-15. Trần Văn Trị, Trần Thanh Hải, 2011: Late Permian-Mesozoic Sông Hiến - An Châu rift system. In Geology and Earth Resources of Việt Nam (Trần Văn Trị and Vũ Khúc - Editors), pp.422-425. Publ. House for Science and Technology, 645pp.